Edukasi Stop Buang Air Besar Sembarangan (BABS) Sebagai Upaya Pencegahan Stunting pada Anak Sekolah Dasar di Kabupaten Langkat - Febriyanti, Eka; Khairani , Leylia; Hajar, Siti (Jurnal SOLMA, 2023)
Background: Stunting has major short- and long-term impacts on health, intelligence, and even productivity. The acceleration of stunting reduction in various regions continues to be promoted through various programs, collaborations and funding in the form of specific and sensitive nutrition interventions. This community service in the form of education to stop open defecation aims to carry out nutrition-sensitive interventions in stunting prevention. Method: Video screening and interactive counseling to 37 children at SDN 054866 Sidomulyo village, Langkat Regency, North Sumatra. In this activity, the dangers of open defecation and the importance of maintaining cleanliness to avoid various diseases, school children also simulated 6-step hand washing. Results: Stop defecation education activities run smoothly and can increase the knowledge of school children about the importance of maintaining cleanliness including not defecating carelessly so that they can avoid various infectious diseases and can grow optimally. Conclusion: This activity is able to increase the knowledge of school children and needs to be carried out continuously in partner schools and other schools, especially in stunting locus areas.